Pengaruh Atribut Produk, Iklan dan Kelompok Acuan terhadap Keputusan Perpindahan Merek dari Sepeda Motor Merek Lain ke Merek Honda (Studi pada Konsumen CV Cendana Motor Cepiring Kendal) - Viana, Rizki; Wartini, Sri (Management Analysis Journal, 2016)
Viana Rizki. 2015. âThe Influence of Product Attributes, Advertising, and Reference Group to the Decision of Brand Switching From Other Brands of Motorcycle to Honda Brand (A Study on Consumers of CV Cendana Motor Cepiring Kendal). Final Project. Management Department. Faculty of Economics. Semarang State University. Advisor. Sri Wartini, S.E., M.M.   This research is motivated by the emergence of the phenomenon of the increasing use motorcycle of Honda brand compared to the other brands. It can encourage consumers to switch to motorcycle of Honda. The problem in this research is there any influence of product attributes, advertising, and reference groups to the brand switching partially or simultaneously. The purpose of this study is to investigate the influence of product attributes, advertising, and reference groups to the brand switching partially or simultaneously. The population of this study is all consumers of CV Cendana Motor Cepiring, Kendal. The sample of this research was determined using iterations formula method with a total of 116 respondents using Purposive Sampling. The data collection methods of this study was questionnaires. The data analysis used in this study was descriptive analysis, classical assumption and multiple linear regression analysis using SPSS 21. The regression analysis resulted the equation, Y= -5.351 + 0.388 X1 + 0.299 X2 + 0.419 X3. Based on partial hypothesis testing the results of partially, product attributes, advertising and reference groups give positive influence to the brand switching decision. While the results of simultaneous hypothesis test show that product attributes, advertising, and reference groups give positive effect on the brand switching decision. It can be concluded from this study that the higher the frequency of product attributes, advertising and the influence of the reference groups, the higher the decision to switch to Honda motorcycle. Advise for companies are suggested to convey input regarding productâs attributes to Hondaâs producer, maintaining the effort advertising, and maintaining the marketing effort through agents or reference groups. Suggestion for the future researchers is to add another independent variables and expand the object of research by comparing other brands that have the same characteristics, such as comparing brand gadget and fashion.